2011
DOI: 10.1128/jb.01390-10
|View full text |Cite
|
Sign up to set email alerts
|

The Sporulation Protein SirA Inhibits the Binding of DnaA to the Origin of Replication by Contacting a Patch of Clustered Amino Acids

Abstract: Bacteria regulate the frequency and timing of DNA replication initiation by controlling the activity of the replication initiator protein DnaA. SirA is a recently discovered regulator of DnaA in Bacillus subtilis whose synthesis is turned on at the start of sporulation. Here, we demonstrate that SirA contacts DnaA at a patch of 3 residues located on the surface of domain I of the replication initiator protein, corresponding to the binding site used by two unrelated regulators of DnaA found in other bacteria. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 31 publications
0
79
0
Order By: Relevance
“…Spo0A activates sirA transcription, and SirA blocks further initiation of DNA replication by binding to DnaA (41,51). Inactivation of sirA causes overinitiation of replication (40,51).…”
Section: Discussionmentioning
confidence: 99%
“…Spo0A activates sirA transcription, and SirA blocks further initiation of DNA replication by binding to DnaA (41,51). Inactivation of sirA causes overinitiation of replication (40,51).…”
Section: Discussionmentioning
confidence: 99%
“…Using this checkpoint, the cell ensures that the 2C DNA content is maintained (322,323,433). The sirA gene was identified in the Spo0A regulon and found to inhibit DNA replication initiation (322,323,433). In addition, it was shown that artificial expression of sirA during vegetative growth caused a block in DNA replication initiation (322,433).…”
Section: Siramentioning
confidence: 99%
“…Using this checkpoint, the cell ensures that the 2C DNA content is maintained (322,323,433). The sirA gene was identified in the Spo0A regulon and found to inhibit DNA replication initiation (322,323,433).…”
Section: Siramentioning
confidence: 99%
See 2 more Smart Citations